Ultrawideband Vivaldi Antenna With an Integrated Noise-Rejecting Parasitic Notch Filter for Online Partial Discharge Detection - Kameli, Sayed Mohammad; Refaat, Shady S.; Abu-Rub, Haitham; Darwish, Ahmad; Ghrayeb, Ali; Olesz, Marek (IEEE transactions on instrumentation and measurement, 2024)
Power transformers and gas-insulated switchgear (GIS) play crucial roles in electrical power grids. However, they may suffer from degradation of insulation material due to wear and tear, leading to their imminent failure. Partial discharges (PDs) are an initial sign of insulation materials degradation, which emit signals spanning various physical domains, including electromagnetic. PDs are temporally narrow, high-frequency, stochastic radiation sources. The ultrawideband (UWB) Vivaldi antenna is the key element for the detection of PDs in power transformers and GIS. However, they may be subject to different interference environments due to external sources of telecommunication radiation noise occupying the 2.4-2.5 GHz band. Noise mixing with PD signals is challenging to resolve, especially for external sensors. Wireless fidelity (Wi-Fi) and Bluetooth signals from mobile devices easily overshadow faint PD signals. Band-reject frequency filters may be attached to the antenna, often at the detriment of the insertion loss. The integrated filter does not require any additional post-processing, making it less computationally demanding for smaller processors used in practice. Wi-Fi and Bluetooth degrade the PD signal, necessitating an integrated analog notch filter for noise removal. Therefore, an external UWB Vivaldi antenna with an integrated noise-rejecting parasitic notch filter is designed, fabricated, and tested to detect PDs in electrical assets such as transformers, power cables, and GIS, with GIS being the focus in the experimental validation in this study. A comparative study of the proposed antenna is presented. This article proposed an antenna that is designed to provide coverage of 95.516% of the 0.226-3.506 GHz frequency band, with an average return loss (RL) of −16.04 dB and a peak gain of 5.5 in the working band, excluding the notched band. The peak RL in the 2.4-2.5 GHz rejection band is −2.68 dB, with an average attenuation of −35.74 dB. This wide coverage is demonstrated in this article using simulation and experiment.